2021
DOI: 10.1101/2021.08.17.456647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleosome-directed replication origin licensing independent of a consensus DNA sequence

Abstract: Saccharomyces cerevisiae has been a faithful guide for study of eukaryotic DNA replication, as the numerous initiation and elongation proteins are conserved from yeast to human. However, there is a gap in our knowledge of why yeast uses a consensus DNA sequence at replication origins, while higher eukaryotes do not. The current study closes this gap. By direct single-molecule visualization, we show that the Origin Recognition Complex (ORC) searches for and stably binds nucleosomes, and that nucleosomes funtion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…It is possible that ORC uses ATP hydrolysis to actively manipulate chromatin structure. Supporting this idea, recent work showed that ORC can evict H2A-H2B dimers 33 .…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that ORC uses ATP hydrolysis to actively manipulate chromatin structure. Supporting this idea, recent work showed that ORC can evict H2A-H2B dimers 33 .…”
Section: Discussionmentioning
confidence: 93%